Contemplative pace and practice of ministry leadership - Masterson, Russ (Covenant Theological Seminary, 2026)
Includes abstract.; D. Min. Covenant Theological Seminary 2026; Includes bibliographical references (leaves 148-154); 1 online resource (viii, 154 leaves)